2016
DOI: 10.1111/jphp.12566
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic activity of 11-O-(4′-O-methyl galloyl)-bergenin and Crassula capitella extract in rats

Abstract: Crassula capitella is a new natural and abundant source for 11-O-(4'-O-methyl galloyl)-bergenin for resolving chronic inflammatory diseases as RA through antioxidant, anti-inflammatory and membrane stabilizing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…Bergenin is a bioactive compound derived from many medicinal plants. Bergenin shows hepatoprotective ( Xiang et al., 2020 ), antioxidant ( Zhang et al., 2022a ), anti-arthritic ( El-Hawary et al., 2016 ), antidiabetic ( Kumar et al., 2012 ), anticancer ( Shi et al., 2021 ), and antiviral activity ( Tomimori, 2000 ). Umifenovir hydrochloride (Arbidol) is a broad-spectrum antiviral drug, which could effectively resist Influenza A Virus and SARS-CoV-2 in vitro ( Wang et al., 2020 ; Li et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bergenin is a bioactive compound derived from many medicinal plants. Bergenin shows hepatoprotective ( Xiang et al., 2020 ), antioxidant ( Zhang et al., 2022a ), anti-arthritic ( El-Hawary et al., 2016 ), antidiabetic ( Kumar et al., 2012 ), anticancer ( Shi et al., 2021 ), and antiviral activity ( Tomimori, 2000 ). Umifenovir hydrochloride (Arbidol) is a broad-spectrum antiviral drug, which could effectively resist Influenza A Virus and SARS-CoV-2 in vitro ( Wang et al., 2020 ; Li et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they were treated with the extract (250 mg/kg) and 11- O- (4′- O- methyl galloyl)-bergenin (5, 10, and 20 mg/kg). The findings indicated that both treatments inhibited the production of pro-inflammatory cytokines, and serum levels of RF and antiCCP were normalized, with an IC 50 of 250 mg/kg for the extract and 20 mg/kg for 11- O- (4′- O- methyl galloyl)-bergenin [ 176 ].…”
Section: Biological and Pharmacological Activities Of Bergeninmentioning
confidence: 99%
“…A literatura existente sugere que as atividades anti-inflamatórias, antitumoral e de citoproteção da bergenina tem impulsionado novas pesquisas. Notavelmente, todos os oito artigos sobre inflamação relataram associações da bergenina quanto à diminuição de citocinas próinflamatórias em colite, bronquite crônica e artrite (14,15). Nessa perspectiva, os estudos deram luz a uma nova possível classe de medicamentos com variadas aplicações à base de um produto natural.…”
Section: Atividade Farmacológicaunclassified
“…A atividade anti-inflamatória foi descrita para o composto isolado pela primeira vez de Crassula capitella identificado como 11 -O-(4'-O metil galoil)-bergenina, o qual foi capaz de reduzir a progressão e gravidade da artrite reumatóide em ratos, por meio de mecanismo antioxidante, antiinflamatório e estabilizador de membrana (14). Um derivado da bergenina, o metilbergenina, extraído da Ardisia japonica, apresentou promissora atividade anti-inflamatória ao inibir a produção de óxido nítrico em macrófagos murinos RAW 264.7 estimulados por lipolissacarídeos (16).…”
Section: Atividade Anti-inflamatóriaunclassified